Profibrotic epithelial TGF-β1 signaling involves NOX4-mitochondria cross talk and redox-mediated activation of the tyrosine kinase FYN - Veith, Carmen; Hristova, Milena; Danyal, Karamatullah; Habibovic, Aida; Dustin, Christopher M.; McDonough, John E.; Vanaudenaerde, Bart M.; Kreuter, Michael; Schneider, Marc; Kahn, Nicolas; van Schooten, Frederik J.; Boots, Agnes W.; et al. (American journal of physiology. Lung cellular and molecular physiology, 2021)
Idiopathic pulmonary fibrosis (IPF) is characterized by a disturbed redox balance and increased production of reactive oxygen species (ROS), which is believed to contribute to epithelial injury and fibrotic lung scarring. The main pulmonary sources of ROS include mitochondria and NADPH oxidases (NOXs), of which the NOX4 isoform has been implicated in IPF. Non-receptor SRC tyrosine kinases (SFK) are important for cellular homeostasis and are often dysregulated in lung diseases. SFK activation by the profibrotic transforming growth factor-β (TGF-β) is thought to contribute to pulmonary fibrosis, but the relevant SFK isoform and its relationship to NOX4 and/or mitochondrial ROS in the context of profibrotic TGF-β signaling is not known. Here, we demonstrate that TGF-β1 can rapidly activate the SRC kinase FYN in human bronchial epithelial cells, which subsequently induces mitochondrial ROS (mtROS) production, genetic damage shown by the DNA damage marker γH2AX, and increased expression of profibrotic genes. Moreover, TGF-β1-induced activation of FYN involves initial activation of NOX4 and direct cysteine oxidation of FYN, and both FYN and mtROS contribute to TGF-β-induced induction of NOX4. NOX4 expression in lung tissues of IPF patients is positively correlated with disease severity, although FYN expression is down-regulated in IPF and does not correlate with disease severity. Collectively, our findings highlight a critical role for FYN in TGF-β1-induced mtROS production, DNA damage response, and induction of profibrotic genes in bronchial epithelial cells, and suggest that altered expression and activation of NOX4 and FYN may contribute to the pathogenesis of pulmonary fibrosis.